EFEKTIFITAS PENDIDIKAN KESEHATAN TENTANG ASI EKSLUSIFTERHADAP PENGETAHUAN IBU DALAM PEMBERIAN ASI EKSLUSIF PADA IBU BEKERJA - Yana " Triani; Misrawati " "; Erwin " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract   Breast milk ( ASI ) is an emulsion of fat in protein, lactose and organic salts secreted by both of mother’s breast glands, serve as the main food for baby. The aims of this study was to determine the effectiveness of health education to the mother’s knowledge in giving exclusive breastfeeding in working mother. Health education has became one of the alternatives to improve mother’s knowledge of exclusive breastfeeding. The design of this reseach study was ‘’ quasy experiment ‘’ with one group pre tets – post test design. The study was conducted in puskesmas koto Kampar Hulu RW 02 and 04 Tanjung villages Kampar district. The sampling method is used purposive sampling with 30 respondents. The analysis were univariate and bivariate frequency test table using Wilcoxon. The result  showed that healt  education is effective to increase mother’s knowledge in breast-feeding exclusively in  working mother with  P value (0.000)< α (0.05). The results of  this study recommend the health service in order to carry out health education on exclusive breastfeeding with routine scheduling so  that the health education given can be more effective.   Keywords: Breast milk, health education, knowledge.